(untitled) (Educational Dimension, 2021)
This review explores how Moodle’s machine learning capabilities enhance adaptive learning. We analyze five studies using Moodle for predictive and prescriptive support in education. These studies cover topics like learner classification, early risk detection, predictor comparison, reliability analysis, and custom indicators. We extract key findings, and address challenges while suggesting future research directions. This review offers insights for educators and researchers aiming to personalize education with Moodle.